Finance for IT decision makers : a practical handbook - Blackstaff, Michael, 1939- (London ; UK : British Computer Society (BCS), 2012)
This edition covers aspects of finance crucial to professionals in both business and non -commercial organisations who make or influence decisions about IT. It takes the reader step by step, in plain language and with many practical examples, through IT relevant financial topics.
Includes index.
First edition published by Springer verlag 1999.
uaj 04/12/2013
Loan
Keywords: Business enterprises -- Finance; Information technology -- Finance